Physical exercise as cytokine modulator in inflammatory immune response: a systematic review - Pertiwi, Kartika Ratna; Yulianti, Evy; Rustiasari, Ukhti Jamil (Jurnal Keolahragaan, 2022)
Physical exercise contributes to maintain our health, through its role in inflammatory immune response. Cytokines are proteins that mediate communication between immune cells, either as pro- or anti-inflammation agents. Nonetheless, the dominance of pro- over anti-inflammatory cytokines during a workout, is harmful to health. This systematic review aimed at determining the effect of physical activity in modulating pro- and anti-inflammatory cytokines during immune response. Following Preferred Reporting Items for Systematic Reviews (PRISMA) guideline, literature searching was conducted in 3 databases which were PUBMED/MEDLINE, DOAJ and GARUDA, using keywords, citation tracking and snowballing. Inclusion and exclusion criterias were used to screen, while the Newcastle Ottawa Scale (NOS) was used to assess the quality of the articles. Data extraction and analysis were conducted descriptively. There were 376 articles identified, of which 329 were sorted and 82 were retrieved. Thirty articles underwent quality assessment, resulting to 12 inclusion studies. In conclusion, physical exercise influences the modulation of cytokine, whereby IL-6 and TNF-Î± (pro-) which increase at the beginning of exercise, are balanced by the increase of IL-10 (anti-inflammatory), which appears later in exercise or during recovery. For this purpose, physical exercise is recommended as a combination of aerobic and resistance exercise performed regularly at moderate intensity.